VBNC Cronobacter sakazakii survives in macrophages by resisting oxidative stress and evading recognition by macrophages - Yuanyuan Liu; Jingfeng Zhang; Haoqing Zhao; Feifeng Zhong; Jianyu Li; Lichao Zhao (BMC Microbiology)
Abstract Survival in host macrophages is an effective strategy for pathogenic bacterial transmission and pathogenesis. Our previous study found that viable but non-culturable (VBNC) Cronobacter Sakazakii (C. sakazakii) can survive in macrophages, but its survival mechanism is not clear. In this study, we investigated the possible mechanisms of VBNC C. sakazakii survival in macrophages in terms of environmental tolerance within macrophages and evasion of macrophages recognition. The results revealed that VBNC C. sakazakii survived under oxidative conditions at a higher rate than the culturable C. sakazakii. Moreover, the stringent response gene (relA and spoT) and the antioxidant-related genes (sodA, katG, and trxA) were up-regulated, indicating that VBNC C. sakazakii may regulate antioxidation through stringent response. On the other hand, compared with culturable C. sakazakii, VBNC C. sakazakii caused reduced response (Toll-like receptor 4) in macrophages, which was attributed to the suppression of biosynthesis of the lipopolysaccharides (LPS). Furthermore, we found that ellagic acid can reduce the survival rate of bacteria in macrophages by improving the immune TLR4 recognition ability of macrophages. In conclusion, VBNC C. sakazakii may survive in macrophages by regulating oxidative tolerance through stringent response and altering LPS synthesis to evade TLR4 recognition by macrophages, which suggests the pathogenic risk of VBNC C. sakazakii.